1987
DOI: 10.1073/pnas.84.24.9243
|View full text |Cite
|
Sign up to set email alerts
|

Specific expression of the pS2 gene in subclasses of breast cancers in comparison with expression of the estrogen and progesterone receptors and the oncogene ERBB2.

Abstract: The expression of the pS2 gene, which is induced by estrogen in the breast cancer cell line MCF-7, has been investigated in breast cancers by using pS2 mRNA determination in tumor specimens and immunocytochemistry to identify pS2 protein in paraffin-embedded sections. Using these assays we show that determination of pS2 gene expression allows the definition of subclasses of estrogen-receptor-containing breast cancers that may be used to more precisely identify estrogen-dependent tumors. Tumor specimens have al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
135
2
4

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(154 citation statements)
references
References 17 publications
13
135
2
4
Order By: Relevance
“…pS2 expression was detected in 29% of the breast cancers studied, which is within the range (22-58%) for mRNA detection in breast cancer reported by others (Rio et al, 1987;Stack et al, 1988;Skilton et al, 1989;Henry et al, 1990;Zaretsky et al, 1990;Hahnel et al, 1991;Delvenne et al, 1992;Wysocki et al, 1994) and similar to the range of 27-68% of breast cancers that express pS2 protein (Foekens et al, 1990;Henry et al, 1991;Schwartz et al, 1991;Walker et al, 1995;Tutschek et al, 1996). The more recent development of reverse transcription polymerase chain reaction (RT-PCR), which may be a more sensitive method to detect pS2, allows both the detection and quantification of pS2 mRNA expression (Carr et al, 1995).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…pS2 expression was detected in 29% of the breast cancers studied, which is within the range (22-58%) for mRNA detection in breast cancer reported by others (Rio et al, 1987;Stack et al, 1988;Skilton et al, 1989;Henry et al, 1990;Zaretsky et al, 1990;Hahnel et al, 1991;Delvenne et al, 1992;Wysocki et al, 1994) and similar to the range of 27-68% of breast cancers that express pS2 protein (Foekens et al, 1990;Henry et al, 1991;Schwartz et al, 1991;Walker et al, 1995;Tutschek et al, 1996). The more recent development of reverse transcription polymerase chain reaction (RT-PCR), which may be a more sensitive method to detect pS2, allows both the detection and quantification of pS2 mRNA expression (Carr et al, 1995).…”
Section: Discussionsupporting
confidence: 85%
“…pS2 expression was significantly related to oestrogen receptor protein expression as expected for an oestrogen-regulated protein (Rio et al, 1987;Stack et al, 1988;Skilton et al, 1989;Henry et al, 1991;Schwartz et al, 1991;Predine et al, 1992;Thompson et al, 1993;Detre et al, 1994;Foekens et al, 1994;Speiser et al, 1994;Stonelake et al, 1994;Walker et al, 1995;Gibert et al, 1996;Tutschek et al, 1996) and we have confirmed the observations of others that pS2 expression (whether measured as mRNA or protein) is not significantly associated with tumour size or node status (Foekens et al, 1990;Schwartz et al, 1991;Delvenne et al, 1992;Gion et al, 1993).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Neither the pS2 peptide nor the pS2 mRNA have been found in significant amounts in normal breast tissue of women [21]. The pS2 peptide is also absent from the breast tissue late in pregnancy, during lactation, and in human milk [20].…”
mentioning
confidence: 91%
“…In human breast tumours, pS2 expression is correlated to OR expression and is a marker of oestrogendependent breast cancer (Rio et al, 1987;Foekens et al, 1994). The human 3366 tumour expresses pS2 mRNA, although at a very low level compared to MCF-7 cells.…”
Section: Oestrogen Receptor Dependent Gene and Protein Expressionmentioning
confidence: 99%